A MULTI-MODAL APPROACH TO QUALITY IMPROVEMENT: REDUCING 'DOOR-TO-CT' TIME IN POTENITALLY THOMBOLYSABLE STROKE PATIENTS. Issue 12 (18th November 2016) - Waterson, F; Braithwaite, I; Tuck, I; Alcock, R
Abstract : Objectives & Background: With 1.9 million neurons lost every minute a stroke is untreated1, rapid assessment and management is a time critical medical emergency, and is reliant on robust Emergency Department (ED) systems. Rapid access to CT imaging is an immediate priority to allow exclusion of patients with haemorrhagic stroke, an absolute contraindication to thrombolysis. Our QI project aimed to reduce the time from arrival in ED to CT scan for patients presenting with potentially thrombolysable stroke. Methods: Using a combination of live and simulated stroke scenarios, we process-mapped the care of potentially thrombolysable patients through the ED at Forth Valley Royal Hospital. We identified 'unnecessary' delays from non-value adding activity and following consultation with the Scottish Ambulance Service, Radiology & Neurology, created a new pre-alert procedure and streamlined protocol for this patient group which facilitated rapid assessment, stabilization and early access to CT imaging. We used a multi-modal approach to deliver change which included weekly clinical governance meetings, teaching for medical & nursing staff, in-situ simulation to educate and stress the system, regular safety brief announcements and the development of a 'Stroke Awareness Week' at our hospital. Results: Door to CT time was reduced by 40%, from 30 minutes (median 23) to 18 minutes (median 13), comparing 4 month sample periods before and after changes. During our QI project, Door-to-Needle (DTN) time has reduced from a mean of 81 minutes (in 2015) to a mean of 64 minutes (2016YTD). Conclusion: Early thrombolysis has been shown to improve outcomes in patients with ischaemic stroke.2 Reducing 'Door-to-CT' scan time in the ED is an important step in enabling a reduction in the overall DTN time. This can be achieved by stream-lining key processes in the patient journey through the ED. A multi-modal approach ensured this change was introduced safely and effectively whilst re-enforcing a core change to standard working practice. Further work on process mapping and the delivery of thrombolysis is the next obvious step in further reduction in DTN time.Figure 1